THE LEARNING IN MAKEUP AND FASHION COURSE AS AN EDUCATION IN PRESERVING JAVANESE CULTURE FOR THE STUDENTS OF LOCAL LANGUAGE AND LETTERS IN VETERAN BANGUN NUSANTARA UNIVERSITY OF SUKOHARJO - Sawitri Sawitri (Proceeding of International Conference on Art, Language, and Culture, 2017)
Learning is an attempt of helping teaching-learning process to achieve the objective of improving high-quality and professional learning in long term. Makeup and fashion are courses intended to Javanese language students in Veteran Bangun Nusantara University aiming to introduce Javanese culture and its application to daily life within family, society and education realm. Not only Javanese cultural preservation can be done through dance, gamelan, gendhing, and Javanese song (tembang Jawa), but also learning through makeup and fashion is very important as the attempt of introducing the students to fashion and makeup in Javanese custom, including wiru (wiron) for male and female, eyebrow shape, shading, paes shape, and kebaya, kuthu baru, stagen, selop, gelung, sunggar and etc in Javanese fashion. Preservation is very desirable to the existence of culture for the next generation, moreover Javanese Language students as the prospect teachers of language and culture that will interact directly with the students. Thus they should have a good understanding on Javanese culture in order to teach it correctly to the students.